Reconstruction of the Politics of Sharia Economic Law in Waqf Regulation in Indonesia - Noor Rizqi, Muhammad; Maksum, Muhammad; Mahmudi, Ibnu Aqil (ASAS, 2025)
The development of waqf regulation in Indonesia demonstrates a significant reconstruction of the politics of sharia economic law. Since the enactment of Law Number 41 of 2004 on Waqf and its implementing regulations, the paradigm of waqf has shifted from a form of charitable religious practice toward a productive instrument of economic development. The state has not only strengthened waqf institutions through the establishment of the Indonesian Waqf Board (Badan Wakaf Indonesia/BWI), but has also expanded the forms and management of waqf in line with modern economic dynamics, including cash waqf, corporate waqf, share waqf, and digital waqf. This transformation reflects political–legal intervention in integrating sharia values into national economic policy. This study aims to analyze the reconstruction of the politics of sharia economic law through waqf regulation in Indonesia by examining the relationship between sharia idealism and the state’s economic development interests. The research employs a political–legal approach using normative–sociological analysis of waqf legislation and its socio-economic context. The findings indicate that waqf policy in Indonesia represents a model of pragmatic idealism, namely a compromise between maqāṣid al-sharī‘ah and the state’s orientation toward economic productivity. The novelty of this study lies in positioning waqf as a policy laboratory for sharia economic law that is adaptive to contemporary economic conditions. This research contributes to the discourse on the politics of sharia economic law and recommends strengthening the balance between the spiritual values of waqf and the objectives of sustainable economic justice.